Mindfulness-Based Interventions for the Treatment of Substance and Behavioral Addictions: A Systematic Review - Sancho, Marta; De Gracia, Marta; Rodríguez, Rita C.; Mallorquí-Bagué, Núria; Sánchez-González, Jéssica; Trujols, Joan; Sánchez, Isabel; Jiménez-Murcia, Susana; Menchón, Jose M. (Frontiers in Psychiatry, 2018)
Background: Emotion (dys)regulation as well as the interventions for improving these difficulties have received growing attention in the literature. The aim of the present paper was to systematically review current evidence on the clinical changes and benefits related to mindfulness-based interventions (MBIs) in both substance and behavioral addictions. Method: A literature search was conducted using Cochrane, PubMed and Web of Science. Fifty-four randomized controlled trials published in English since 2009 to April 2017 were included into a narrative synthesis. Results: MBIs were applied in a wide range of addictions, including substance use disorders (from smoking to alcohol, among others) and behavioral addictions (namely gambling disorder). These treatments were successful for reducing dependence, craving and other addiction-related symptoms by also improving mood state and emotion dysregulation. Among the most commonly used MBIs approaches were: Mindfulness-Based Relapse Prevention (MBRP), Mindfulness Training for Smokers (MTS) or Mindfulness-Oriented Recovery Enhancement (MORE) and the most frequent control group in the included studies was Treatment as Usual (TAU). The most effective approach was the combination de MBIs with TAU or other active treatment. However, there is a lack of studies showing the maintenance of the effect over time. Therfore, studies with longer follow-ups are needed. Conclusions: The revised literature shows support for the effectiveness of the mindfulness-based interventions. Future research should focus on longer follow-up assessments as well as on adolescence and young population, as they are a vulnerable population for developing problems associated with alcohol, drugs or other addictions. Key words: mindfulness, addiction, behavioral addiction, substance use, gambling.